'I was listening … but did not succeed in hearing you': Flann O'Brien, Ralph Cusack, and the Absurdities of Silent Musical Experience. Issue 2 (November 2021) - Erraught, Stan
Abstract : The notion of soundless music seems contradictory, even absurd: the concept of soundless musical experience less so. In this article, I explore two quite different descriptions of this kind of experience as set out in two mid-twentieth-century Irish novels. In one, Flann O'Brien's The Third Policeman, the narrator watches one of the titular sergeants enjoy music that he – the narrator – cannot hear. In the second, Ralph Cusack's Cadenza, the narrator watches as a village priest mimes playing the piano on a café table, a performance he 'hears' and appreciates. Speculatively combining and extending these episodes, and using the figures of the philistine and the aesthete in Adorno's Aesthetic Theory as a key, I suggest that an anxiety about music and musical expression characterized the newly independent Ireland, an anxiety linked to wider concerns often read as 'postcolonial'.